THE STUDY OF PROBABILISTIC CHARACTERISTICS OF POWER SUPPLY SYSTEMS - E. I. Gracheva; R. R. Sadykov (Известия высших учебных заведений: Проблемы энергетики)
The article describes the algorithm of modeling of probabilities of condition of power supply. The developed model estimates the  probabilistic characteristics of the elements of power supply systems rehabilitation and prevention.